Analog of the black-scholes formula for option pricing under conditions of (B, S, X)-incomplete market of securities with jumps - Zhuravyts'kyi, D. G.; Kalemanova, A. V.; Svishchuk, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We describe a (B, S,X )-incomplete market of securities with jumps as a jump random evolution process that is a combination of an ltô process in random Markov medium and a geometric compound Poisson process. For this model, we derive the Black-Scholes equation and formula, which describe the pricing of the European call option under conditions of (B,S,X)-mcomplete market.